Data-driven model identification of guided wave propagation in composite structures - da Silva, Samuel [UNESP] (Springer Nature, 2018)
This paper shows the applicability of data-driven model identification to describe guided wave propagation in composite structures. The model identified can be useful to predict waveform or further conditions considering the dynamics of wave propagation in composites media, mainly when the geometry or boundary conditions are complex and make it very difficult to propose an analytical model. Thus, the main purpose of this paper is to use a simple autoregressive with exogenous terms model to fit the experimental data assuming different frequencies of excitation and the effect of temperature changes. An example using a composite plate is performed in this paper to show the steps and applicability. After these analyses, the results obtained demonstrate the practical benefits of the black-box model for modeling of guided wave propagation in complex composite structures for aeronautical applications.
Keywords: ARX model; Composite structures; Guided wave propagation; Lamb wave; System identification